Elements of architecture - Koolhaas, Rem, 1944- (Köln : Taschen, 2018)
Never was a book more relevant - at a moment when architecture is changing beyond any recognition, it offers stunning insight into the lost histories of its humble but essential elements, from the stone age to our confusing present...
Keywords: Architectuur